A study on the appropriateness of applying the Kaizen method in continuous improvement, reducing costs, and maximizing achievement - Khan, Osamh Ibrahim; Baqader, Saleh Mohammed Saleh (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to review previous studies that examine the impact of applying the Kaizen methods in reducing costs, maximizing achievement in organizations, and identifying the importance of applying Kaizen for continuous improvement in Companies. The study confirmed that applying the Kaizen method allows companies to reduce costs, continuously improve, and maximize achievement. The study recommends that companies consider applying the Kaizen method to reduce costs and maximize achievement. In addition, companies should provide training for the employees to understand the mechanisms of Kaizen and its applications.